2013
DOI: 10.5301/ejo.5000243
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane Transplantation in Treatment of Persistent Corneal Ulceration after Severe Chemical and Thermal Eye Injuries

Abstract: Amniotic membrane transplantation may stop ulceration and promote corneal epithelialization in the majority of patients with the most severe chemical or thermal eye injuries in case of timely application of the operation and adequate fixation of the AMT graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Healing of this condition can be achieved by ATM. There are numbers of publications demonstrating that application of AM lead to improved or complete healing of the corneal ulcers (30,31,32,33,34). Again, our study confirmed the literature observations, as we reported here, that application of AM to our seven groups, which includes the major ophthalmological diseases, can severely improve the size of a corneal ulcer.…”
Section: Discussionsupporting
confidence: 91%
“…Healing of this condition can be achieved by ATM. There are numbers of publications demonstrating that application of AM lead to improved or complete healing of the corneal ulcers (30,31,32,33,34). Again, our study confirmed the literature observations, as we reported here, that application of AM to our seven groups, which includes the major ophthalmological diseases, can severely improve the size of a corneal ulcer.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, treatment with glycerinepreserved amniotic membranes was less efficacious than described previously by different groups (Kruse et al 1999;Chen et al 2000;Prabhasawat et al 2001;Letko et al 2001;Fereira de Souza et al 2001;Dogru et al 2003;Chen et al 2006;Nubile et al 2011;Iakimento et al 2013;Berguiga et al 2013) . This may be due to the retrospective nature of our analysis: our patients were not regularly investigated, so treatment failures may have been diagnosed late.…”
Section: Discussionmentioning
confidence: 69%
“…Iakimento et al. () stated a re‐epithelialization rate of 76% of 55 eyes with corneal ulcers and limbal insufficiencies that had been treated with glycerine‐preserved amniotic membranes. They also reported that 12.5% of the corneas that did not epithelialize required reoperation and found later recurrence in 14.3% of re‐epithelialized corneas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations